An experimental investigation on flash butt welded rails. (November 2015) - Ozakgul, Kadir; Piroglu, Filiz; Caglayan, Ozden
Abstract: In this paper, experimental studies performed for flash butt welded rails used in Turkish railways network having 49E1 and 60E1 rail sections are presented. These studies comprise of full-scale laboratory tests such as four point bending fatigue and three-point slow bending tests, as well as related instrumentation of test specimens and data measurement. Fatigue and bending tests are prepared and carried out in accordance with EN 14587-2 standard. The fracture surfaces of the welded samples are examined to identify the associated failure modes. The fatigue test results are superimposed on a S–N diagram derived from earlier results reported as a part of the European Commission steel rails research project. A best fit curve following an exponential function is derived to describe the load deflection behavior of the weld under the slow bend testing conditions. It is shown that a single component of the equation defining the best fit curve is the factor controlling the scattering in the non-linear part of the load deflection curve, and hence control of this parameter can also be used to impart consistency to the welding process. Highlights: We present experimental studies for flash butt welded rails used in Turkish railways. Tests comprise of four point bending fatigue and three-point slow bending tests. The fatigue and bending tests are carried out by using relevant EN standard. Fatigue test results are superimposed on a S–N diagram derived from earlier results. A function is derived to define load-deflection behavior of the weld under bending.